Verbal Imitation Program To Improve Language Production In Children Aged 4 - 6 Years Who Experience Speech Delay At Early Childhood "X" Bandung - Hadiman, Raissa; Gunawan, Yuspendi; Victoriana, Evany (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
The objective of this study is to find out how significant verbal imitation on improving language production in 4-6 years old speech delay children at Kindergarten “X” This study used one group pretest-posttest design, with measuring tools used in this study is developmental milestones of Language Production by Olmstead (1971) and has been modified by the researcher. Expert judges tested the validity and reliability testing of the measuring tools. The samples of this study were 8 children who met the sample characteristics and were selected using purposive sampling techniques. The results of statistical test using Wilcoxon is p = 0.019 < 0.05 with Z = -2.366. It indicates differences in children's language production before and after the child undergoing a verbal imitation program. Theoretical suggestions for further research is to conduct a collaborative study that intervenes both parents and children simultaneously. Practically, parents and teachers should continue providing clear and consistent directions to children to correctly imitate the articulate sound of words. Child practitioners are suggested to consider verbal imitation program as an intervention in dealing with children who have a speech delay.